PEMIKIRAN HASSAN HANAFI TENTANG KRITIK TRADISI ISLAM (ANALISIS HERMENEUTIKA) - Ahmad Efendi Hadirois, Suryo Ediyono (CMES (Center of Middle Eastern Studies), 2015)
This research discussed the renewal concept of Islam according Hassan Hanafi, Legacy Critical of Islam according Hassan Hanafi‟s effort for Renewal of Islam. This research used qualitative method which is presented descriptively by describe condition of Egypt society, personage who influenced Hanafi‟s Philosophy, then describe Hanafi‟s Left Islam Philosophythese are describe Islamic Legacy revitalization, occidendatalism, gesture toward Islamic world reality, The Legacy Critical of Islam, reinterpretation Islamic Legacy, and hermeneutic of al-Qur‟an. Based on the result of this research conclude  are  : first, Islam has a Legacy intellectual there are text‟s, concept‟s, Philosophy be present in reality and take root in society. Second, there is rigidity of muslim think is happened because there is proudly feeling with legacy self. Third, muslim should take a attitude of patient to make resurrection of Islam is back. Fourth, one of the way for aim resurrection of Islam concern with  Hanafi‟s Left Islam Philosophy.